Effect of Carbon Nitrogen (C:N) ratio towards population of bagworm in Ladang Risda Durian Mas 2, Dungun, Terengganu / Muhamad Arif Yusof - Yusof, Muhamad Arif (Faculty of Plantation and Agrotechnology, 2019)
Bagworms (Lepidoptera: Psychidae) is one of the important pest in oil palm plantation industry in Malaysia and this infestation could cause yield to decline from 33% to 40% and can become more severe if no measurement taken to control it. The population of bagworm always related with nitrogen as NPK fertilizer that usually used in plantation sector may affect the bagworm population. This study was conducted to determine the population of bagworm in Ladang Risda Durian Mas 2, Dungun, Terengganu. The data was collected for 7 weeks that start from July until August 2018. Furthermore, the objective of this study is to determine the relationship between carbon nitrogen (C:N) ratio and population of bagworms. As for the leaves sample analysis, the sample will be run using the Thermo Flash 2000 CHNS analyzer. From the sample analysis data, it show moderate negative correlation (-0.343) for the population of bagworm and carbon. However, strong positive correlation (0.649) will produce for nitrogen and bagworm population. This strong correlation means that the increase in nitrogen value will increase the bagworm population. Therefore, the management need to optimize the rate for fertilizer applied by using at recommended dosage and not overuse as it can attract bagworm and other pest. Lastly, if there are symptoms for bagworm infestation the effective controlled measurement must be taken immediately to prevent it from become more serious.